Pendekatan Rasional Muhammaddiyah Terhadap Ilmu Pengetahuan dan Pembentukan Hukum yang Berkeadilan - Azaria Putri Illona; Hikmatul Salwa; Arjun Bangkit Prayoga; Wahdatul Dea Saputri; Astika Nurul Hidayah (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Abstract. Muhammadiyah's rational approach in establishing just law shows the integration of Islamic values ​​with the modern context. This study aims to explore Muhammadiyah's contribution in the formation of maqashid sharia-based law, emphasizing social justice and the relevance of Islamic law in the era of globalization. The research methods used include literature review and document analysis to identify Muhammadiyah's approach to ijtihad and maqashid sharia. The results of the study show that Muhammadiyah's progressive approach has a significant impact in overcoming contemporary legal challenges, such as gender equality and economic justice. This approach also strengthens the global discourse on just Islamic law, by promoting universal principles derived from Islamic values.